As imunidades de jurisdição e execução dos entes do direito público internacional e a garantia dos créditos trabalhistas - Lima, Luciana Moura (2012)
This thesis turns to the positioning of the Brazilian legal system where the worker ever though the credit guarantee labor faces of immunity from jurisdiction or execution of a Being Public International Law. The work in question points out the difference between the immunity from jurisdiction and execution of a being public international law, points out that for each entity the standard provides a different treatment and attempts to demonstrate that this position hurts precepts of human rights guaranteed in international treaties where Federative Republic of Brazil is a signatory. Finally, we analyze the international treaties that deal with human rights can come in the future to have a normative status hierarchical supralegalidad that the doctrine classified as control of conventionality. Thus, certain labor rights play a key role of human rights and become inseparable. positions in volving new control standards and aspects of modern process, especially the process of working to wards the labor credits.